As perspectivas de professor pesquisador em narrativas de egressos do programa de pós - graduação em educação e ensino de ciências na Amazônia - Mota, Elizangela da Rocha (2015)
This research has as object of investigation the redefinition of professor researcher trend by the Academic Master´s course egresses in Science Education in the Amazon the University of the State of Amazonas and the contributions brought to their living and investigative experiences. The subjects of research were six egresses, three Academic Masters and three College Professional Masters. The research is defined as qualitative, legitimated by the technical semistructured interviews and life´s report. The treatment of collected data were based on interpretative analysys divided on four areas: (1) Living and experiences with the master´s degree research; (2) Perspective of the Professor Researcher Trend; (3) The emphasis on Professor Researcher Trend during the Master´s degree training; (4) The Professor researcher trend features on daily work. The analyzed reports allows us to understand that the egresses act as professor researchers, giving a new meaning on their professional practices providing the students an education with research mediated by several strategies, as internship use, field analysis, articles elaboration and realized survey publication. The Master degree as a graduation course provides a variety of knowledge and skills to a transforming educational practice, as the professor researcher graduation, leaving up to them to take or not this position. The route in master´s course resulted in the redefinition of the ontological, epistemological and methodological aspects of the egresses and researcher